Perinatal mental health: the role of social inequalities and domestic abuse on maternal outcomes - Loane, Maria; Given, Joanne; Rosato, Michael; Leavey, Gerry (International Journal of Population Data Science, 2025)
Perinatal mental health conditions (depression, anxiety disorders, and postpartum psychosis/bi-polar disorder) affect one in four new/expectant mothers. We assessed the impact of social inequalities, sociodemographic factors, domestic abuse and maternal interactions with social services in childhood on mortality and morbidity outcomes in women with these conditions in Northern Ireland (NI). We identified a population-based cohort of 179,723 mothers giving birth in NI between 01-01-2010 and 31-12-2022 (301,110 pregnancies). Eight datasets were linked: maternity, death records, prescriptions, hospital episodes/admission/discharges, A&E, mental health inpatient data, social services, and the rateable value of the property of maternal residence during pregnancy. Sociodemographic variables included maternal age, parity, gestational age, single parent family, marital status, employment status, and ethnic group. Domestic abuse was identified from the maternity disclosure variables and A&E data. We will present the: Incidence and prevalence of perinatal mental health conditions occurring during pregnancy and in the first year following birth. Sociodemographic and socioeconomic determinants of perinatal mental health conditions and the impact of these on maternal mortality and morbidity outcomes. Incidence and impact of domestic abuse on maternal mortality and morbidity outcomes in women with perinatal mental health conditions. Relationship between maternal interactions with social services in childhood and maternal mortality and morbidity outcomes in women with perinatal mental health conditions. How multiple adversity (socioeconomic inequalities, socio-demographic factors, maternal interactions with social services in childhood, and domestic abuse) contributes to maternal mortality and morbidity outcomes in these women. This is the first population-wide study to investigate how multiple adversity affects mortality/morbidity outcomes in women with perinatal mental health conditions. The impact of this research will enable early effective support and interventions to be implemented to minimise adverse outcomes in this vulnerable population Data for this project was provided by the HSC Honest Broker Service, within the Business Services Organisation (BSO). The views/ opinions presented are solely those of the author and do not necessarily represent those of the BSO.